Multiple Model Evaluation of the Masseteric-to-Facial Nerve Transfer for Reanimation of the Paralyzed Face and Quick Prognostic Prediction - Li, Tengfei; Liu, Yanhui; Zhang, Shuxin; Yang, Wanchun; Zuo, Mingrong; Liu, Xuesong (Frontiers in Surgery, 2022)
Facial paralysis is negatively associated with functional, aesthetic, and psychosocial consequences. The masseteric-to-facial nerve transfer (MFNT) has many advantages in facial reanimation. The aim is to evaluate the effectiveness of our MFNT technique and define the potential factors predictive of outcome. The authors conducted a retrospective review of 20 consecutive patients who underwent MFNT using the temporofacial trunk of facial nerve. Videotapes and images were documented and evaluated according to Facial Nerve Grading Scale 2.0 (FNGS2.0) and Sunnybrook Facial Grading System (FGS). The quality-of-life was obtained using the Facial Clinimetric Evaluation (FaCE) Scale. Moreover, Facial Asymmetry Index (FAI), width of palpebral fissure, deviation of the philtrum and angles or excursions of the oral commissure were applied to explore the effect of the transfer metrically. Multivariable logistic regression models and Cox regression were prepared to predict the effect of MFNT by preoperative clinical features. Patients showed favorable outcomes graded by FNGS2.0, and experienced significantly improved scores in static and dynamic symmetry with slightly elevated scores in synkinesis evaluated by the Sunnybrook FGS. The score of FaCE Scale increased in all domains after reanimation. The quantitative indices indicated the symmetry restoration of the middle and lower face after MFNT. Regression analysis revealed that younger patients with severe facial paralysis are preferable to receive MFNT early for faster and better recovery, especially for traumatic causes. The findings demonstrate the MFNT is an effective technique for facial reanimation, and case screening based on clinical characteristics could be useful for surgical recommendation.